Matrine Restores Colistin Efficacy Against mcr-1-Carrying Escherichia coli - Zhinan Wang; Xiaowei Li; Liang Zhao; Saiwa Liu; Jingjing Du; Xi Jia; Lirui Ge; Jian Xu; Kexin Cui; Yu Ga; Jinxiu Wang; Xi Xia (Molecules)
The emergence of mcr-1-mediated colistin resistance has become a critical global health concern, highlighting the urgent need for innovative approaches to restore colistin’s therapeutic potential. In this study, we evaluated the antibacterial activity of four matrine-type alkaloids—namely, matrine, oxymatrine, sophocarpine, and sophoramine—against mcr-1-positive Escherichia coli. While these alkaloids showed limited efficacy when used alone, the combination of matrine with colistin exhibited remarkable synergistic effects, as demonstrated by checkerboard assays and time-kill curve analyses. The matrine–colistin combination caused minimal erythrocyte damage while effectively attenuating resistance development in vitro. This synergy was further corroborated in a murine infection model, where the combination significantly reduced bacterial loads in target tissues. Mechanistic studies revealed that the matrine–colistin combination enhances antimicrobial activity by disrupting bacterial membrane integrity, increasing intracellular colistin accumulation, and triggering reactive oxygen species-mediated oxidative damage. Collectively, these findings highlight the potential of matrine as a promising adjuvant to overcome colistin resistance, providing a novel therapeutic approach to address the challenge of infections cause by multidrug-resistant Gram-negative bacteria.